Factors associated with ventilator-associated events: an international multicenter prospective cohort study - Rello, Jordi; Ramírez-Estrada, Sergio; Romero, Anabel; Arvaniti, Kostoula; Koulenti, Despoina; Nseir, Saad; Oztoprak, Nefise; Bouadma, Lila; Vidaur, Loreto; Lagunes, Leonel; Peña-López, Yolanda (European journal of clinical microbiology & infectious diseases, 2019)
A secondary analysis of a prospective multicenter cohort was performed in six intensive care units (ICU) in four European countries (France, Greece, Spain and Turkey). The main objective was to identify factors associated with ventilator-associated events (VAEs) in adults who underwent mechanical ventilation (MV) ≥ 48 h. Secondary objectives were to identify: variables influencing VAE in the subpopulation with endotracheal intubation and in those subjects who were ventilated > 7 days. Subjects who had undergone MV ≥ 48 h were included. In subjects with multiple episodes of MV, only the first one was eligible. The adult definitions for VAEs were adjusted to the 2015 update of the CDC’s 2013 National Healthcare Safety Network Association. Factors associated with VAE were estimated through multivariate Cox proportional hazards analysis. Among 163 adults (42 tracheostomies), 76 VAEs (34.9 VAEs/1,000 ventilator-days) were documented: 9 were Ventilator-Associated Conditions (VAC) and 67 Infection-related Ventilator-Associated Complications (IVAC)-plus (9 only IVAC and 58 Possible Ventilator-Associated Pneumonia). VAEs developed after a median of 6 days (interquartile range: 4–9). VAEs were independently associated with long-acting sedative/analgesic drugs (Hazard Ratio [HR]: 4.30), selective digestive decontamination (SDD) (HR: 0.38), and surgical/trauma admission (HR: 2.30). Among 116 subjects with endotracheal tube, SDD (HR: 0.21) and surgical/trauma admission (HR: 3.11) remained associated with VAE. Among 102 subjects ventilated >7 days, only long-acting sedative/analgesic agents (HR: 8.69) remained independently associated with VAE. In summary, SDD implementation and long-acting analgesic/sedative agents restriction prescription may prevent early and late VAEs, respectively. Bundles developed to prevent VAEs should include these two interventions.